Composition and spatiotemporal distribution of ichthyoplankton on the continental shelf of the southern East China Sea - Yi-Chen Wang Ming-An Lee (Terrestrial, Atmospheric and Oceanic Sciences, 2021)

(untitled)
This study investigated the effects of the Kuroshio Front (KF) on the continental shelf of the southern East China Sea on ichthyoplankton communities during the northeast monsoon period. According to field observations and satellite images of sea surface temperature, we documented that the KF occurred and moved nearshore between December and January before shifting seaward in March. In total, 156 species were identified among the 9896 individual larval fish collected. Multivariate analysis revealed significant differences in fish abundance and composition over time. The abundance of oceanic species increased by approximately 10% from December to January and then decreased by approximately 50% in March. Oceanic species, such as myctophid and gonostomatid fish, were dominant (37.4 - 86.5%) in the oceanic waters on the offshore side of the KF. Some coastal and commercial species, such as anchovies, were dominant (26.9 - 99.1%) in the neritic waters on the nearshore side of the KF from December to March. These results may have been influenced by spawning seasons and adult habitats. The strong front influenced the distribution of larval fish more than the weaker upwelling during winter did. Specifically, oceanic fish were brought into nearshore waters by Kuroshio water intrusion in winter. Most larvae were still restricted to the nearshore and offshore side by the KF, meaning that the strong KF was still a barrier separating most fish larvae assemblages, especially for those of the neritic species. The mechanism underlying the cross-frontal transport of fish larvae is more likely to occur in oceanic species, because it may be related to diel vertical migration behavior.